2016
DOI: 10.1186/s13017-016-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Validity of predictive factors of acute complicated appendicitis

Abstract: BackgroundOur previous retrospective study revealed the three preoperative predictors of complicated appendicitis (perforated or gangrenous appendicitis), which are body temperature ≥37.4 °C, C-reactive protein ≥4.7 mg/dl, and fluid collection surrounding the appendix on computed tomography. We reported here an additional prospective study to verify our ability to predict complicated appendicitis using the three preoperative predictors and thus facilitate better informed decisions regarding emergency surgery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Gangrenous appendicitis is characterized by ischemic regions that cause gangrene of the appendix, while perforation of the appendix is determined by the loss of continuity of the appendix ( 13 ). The histopathology of phlegmonous appendicitis corresponds to uncomplicated appendicitis (AUA), while gangrenous appendicitis and perforation are classified as complicated appendicitis (ACA), as stated in the document ( 13 , 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gangrenous appendicitis is characterized by ischemic regions that cause gangrene of the appendix, while perforation of the appendix is determined by the loss of continuity of the appendix ( 13 ). The histopathology of phlegmonous appendicitis corresponds to uncomplicated appendicitis (AUA), while gangrenous appendicitis and perforation are classified as complicated appendicitis (ACA), as stated in the document ( 13 , 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…25 In clinical settings the histological finding of phlegmonous appendicitis directly corresponds with uncomplicated courses (AUA), whereas gangrenous appendicitis and perforation are categorised as acute complicated appendicitis (ACA), as stated in the literature. 6,25 Correlations between ultrasound findings and histopathological results are visualised in Figure 2.…”
Section: Histopathological Classificationmentioning
confidence: 99%
“…Early detection of complicated appendicitis including gangrene with or without perforation is crucial for timely application of special antibiotic regimens and for estimation of the optimal time point for surgery. 6 Furthermore, this kind of differentiation might even offer the possibility of different treatment options. Nowadays, acute appendicitis is the most common diagnosis of paediatric patients who undergo surgical treatment and patients still experience a remarkably high rate of postoperative complications, despite the fact that most of the procedures are performed objective: This study aims to differentiate acute uncomplicated and complicated appendicitis, by investigating the correlation between sonographic findings and histological results in different types of paediatric appendicitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory tests are performed routinely in most patients. Besides the white blood cell count, a systematic review showed that C-reactive protein level provides the highest diagnostic accuracy (8). Non-invasive, inexpensive, and easy to perform, the ultrasound scan also avoids radiation, but its results are examiner-and patient-dependent.…”
Section: Diagnosing Acute Appendicitismentioning
confidence: 99%